STRATEGI KEMENTERIAN AGAMA DALAM MENINGKATKAN MUTU MANAJEMEN MADRASAH ALIYAH DI KABUPATEN SELUMA - Suhirman Suhirman; Idi Syatriawan (Universitas Islam Negeri Fatmawati Sukarno, 2017)
The purpose of the research is to describe the strategy of the Ministry of Religious Affairs in Improving the Quality of Madrasah Aliyah Management in Seluma District. This type of research includes qualitative research. The subject of this study was head of Seluma, Head of Madrasah and principal. Instrument of data collection using obser- vation, interview and documentation, Technique of data analysis with qualitative data analysis done interactively and progress continuously until complete, so that data is saturated. The results of this study indicate that the strategy of the Ministry of Religious Affairs in improving the quality of Madrasah Aliyah management in Seluma Regency by improving the academic and non academic quality by meeting the 8 national education standards in accordance with the PP. 32Year 2013 which includes content standards, process standards, equipment and infrastructure standards, graduation competency standards, management competency standards, financing competency standards, competency standards of educators and education personnel as well as assessment competency standards. Constraints experienced by the Ministry of Religious Affairs Seluma in improving the quality of Madrasah Aliyah management such as teachers and educators who have not met the academic standards, still low ability to take advantage of IT, and Infrastructure Inad- equate. The solution to overcome obstacles in improving the quality of Madrasah Aliyah management by the Seluma Regency ministry is to motivate teachers to improve their educational qualifications, to include teachers in workshops and training, to activate KKG activities and to use IT such as internet, communication tools and social media Others. Keywords: Strategy, Ministry of Religious Affairs, Quality of Madrasah Aliyah Management.